Could cytokine levels in the peri‐implant crevicular fluid be used to distinguish between healthy implants and implants with peri‐implantitis? A systematic review. (16th January 2016) - Duarte, P. M.; Serrão, C. R.; Miranda, T. S.; Zanatta, L. C. S.; Bastos, M. F.; Faveri, M.; Figueiredo, L. C.; Feres, M.
Abstract : Background and Objective: Despite investigative efforts to identify the levels of different types of cytokines in the peri‐implant crevicular fluid (PICF), the efficacy of these biomarkers in assisting the diagnosis of peri‐implantitis is still undetermined. This systematic review aimed to answer the following question: "Could cytokine levels in the PICF be used to distinguish between healthy implants and implants with peri‐implantitis?" Material and Methods: This review was conducted and reported in accordance with the PRISMA statement. The MEDLINE and EMBASE databases were searched from 1990 up to and including March 2015, using MeSH terms and other keywords. Additional publications were searched using a hand search of reference lists of relevant studies. Titles and abstracts were screened and papers that fulfilled eligibility criteria were assessed. Results: Out of 1212 titles, 18 studies reporting the levels of nine different cytokines were included. Proinflammatory cytokines [interleukin (IL)‐1β, IL‐6, IL‐12, IL‐17 and tumor necrosis factor‐α) were the cytokines studied most commonly, followed by anti‐inflammatory cytokines (IL‐4 and IL‐10), osteoclastogenesis‐related cytokines (RANKL) and chemokines (IL‐8). Nine studies reported statistically significantly higher levels of proinflammatory cytokines in the PICF of implants with peri‐implantitis than in the PICF of healthy implants. Most studies did not find any significant differences in the PICF levels of anti‐inflammatory cytokines and RANKL between healthy implants and implants with peri‐implantitis. IL‐8 was the only chemokine studied and its levels did not differ significantly between healthy and diseased implants. The studies differed greatly in the manner in which they reported the results (e.g. concentrations or total amounts) and in the exclusion of confounders, such as smoking. Conclusion: The results of this systematic review indicate moderate evidence in the literature to support that implants with peri‐implantitis present higher levels of proinflammatory cytokines in the PICF than do healthy implants. Evidence regarding the PICF levels of anti‐inflammatory cytokines, osteoclastogenesis‐related cytokines and chemokines as possible predictors of peri‐implantitis is too limited.